The properties of nano-CaCO3/nano-ZnO/SBR composite-modified asphalt - Li Zhenxia (De Gruyter, 2021)
To solve the problem of the pavement being aged due to the influence of temperature, light and other environmental factors are brought in service. Nano-CaCO3 surface was activated by 6% KH-550, and nano-ZnO surface was activated by 6% aluminate. Nano-CaCO3/nano-ZnO/SBR composite-modified asphalt was prepared. The optimum proportion of composite-modified asphalt was determined by orthogonal test. The influence of modifiers on asphalt pavement performance was comprehensively studied. The microstructure of composite-modified asphalt was characterized by scanning electron microscopy and infrared spectroscopy. The mechanism of composite-modified asphalt was analyzed. The results show that the optimum combination of composite-modified asphalt is 4% nano-CaCO3 + 5% nano-ZnO + 4% SBR, the aging performance of the composite-modified asphalt is reduced by 6.9%, and the viscosity is increased by 14.6–23.1%. The complex shear modulus is increased by 24.1% at 82°C, the stiffness modulus is decreased, on average, by 21.1%. and the creep curve slope is increased by 9% on average. In the meantime, during the preparation process of composite-modified asphalt, it mainly occurred due to chemical reaction with surface-modified nanomaterials and physical change with SBR polymer materials.